2022
DOI: 10.1021/acs.chemmater.1c03014
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Synthesis of Theoretically Predicted Multivalent Ternary Nitride Materials

Abstract: Multivalent ternary nitride materials, which combine two metal cations with a nitrogen anion in equal amounts and charge balanced stoichiometry, tend to have relatively simple structures and promising properties for a broad range of applications. Historically, discovery of such new nitrides has been a bulk synthesis endeavor, following chemical intuition. In the past decade experimental synthesis of theoretically predicted materials, including as thin films, has changed this approach. In this perspective, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 198 publications
3
61
0
Order By: Relevance
“…In photoelectrode co-design, it is critical to consider materials that could be paired with established semiconductors to impart good material quality via heteroepitaxy and have surfaces that transform under operation in aqueous conditions to stable coatings with compatible crystal structures. Recent work in computational materials discovery has predicted a trove of nitride semiconductors with earth-abundant constituent elements that merit evaluation against these criteria. , A family of Zn- or Mg-based multivalent ternaries with crystal structures derived from wurtzite or rocksalt parent compounds , is particularly promising; these nitrides can be integrated with wide-band-gap GaN and related III-N wurtzite semiconductors that are amenable to p-type doping for contact formation. Examples of the experimentally synthesized wurtzite materials in this family include Zn 2 VN 3 , MgSnN 2 , , Zn 2 NbN 3 , Zn 3 MoN 4 , Zn 2 SbN 3 , Mg 2 SbN 3 , Mg 2 PN 3 , and Zn 2 PN 3 , , among others.…”
Section: Introductionmentioning
confidence: 99%
“…In photoelectrode co-design, it is critical to consider materials that could be paired with established semiconductors to impart good material quality via heteroepitaxy and have surfaces that transform under operation in aqueous conditions to stable coatings with compatible crystal structures. Recent work in computational materials discovery has predicted a trove of nitride semiconductors with earth-abundant constituent elements that merit evaluation against these criteria. , A family of Zn- or Mg-based multivalent ternaries with crystal structures derived from wurtzite or rocksalt parent compounds , is particularly promising; these nitrides can be integrated with wide-band-gap GaN and related III-N wurtzite semiconductors that are amenable to p-type doping for contact formation. Examples of the experimentally synthesized wurtzite materials in this family include Zn 2 VN 3 , MgSnN 2 , , Zn 2 NbN 3 , Zn 3 MoN 4 , Zn 2 SbN 3 , Mg 2 SbN 3 , Mg 2 PN 3 , and Zn 2 PN 3 , , among others.…”
Section: Introductionmentioning
confidence: 99%
“…Before performing crystal structure predictions for ABN 2 compositions (A = Mg, Ca, Sr, Zn; B = Sn, Ti, Zr), we have carefully collected all theoretically and experimentally reported structures for these compositions from the ICSD, 62 Materials Project, 54 OQMD, 63 and AFLOW 64 databases and available published literatures. As listed in Table 1, except for SrSnN 2 , the other 11 chemical systems all have thermodynamically stable structures, among which Mg/ZnSnN 2 , 65 Mg/SrZrN 2 , 65,66 and Mg/Ca/Sr/ ZnTiN 2 65,67 have been experimentally synthesized. For each given ABN 2 composition (A = Mg, Ca, Sr, Zn; B = Sn, Ti, Zr), we then used the evolutionary algorithm USPEX software to search their potential crystal structures.…”
Section: ■ Workflowmentioning
confidence: 99%
“…As chemists and materials scientists expand the palette of available materials, interest in new nitrides continues to grow. 1 , 2 The perovskite structure, with the basic formula AB X 3 , underlies the properties and function of materials crucial to fields including solar research, ultrasonics, fuel cells, and many more, but there is a notable lack of reported nitrides with the perovskite structure. A few recent computational studies have predicted the stability of rare earth transition metal nitride perovskites 3 − 6 and interesting ferroic properties such as ferroelectricity in LaWN 3 and ferromagnetism in a broad range of RE M N 3 (RE = rare earth; M = W, Re) compounds.…”
Section: Introductionmentioning
confidence: 99%